Salvadoran imaginaries : mediated identities and cultures of consumption - Rivas, Cecilia M., 1978- (Latinidad., 2014)
Accessible and beautifully written, Rivas examines how El Salvador's post-war identity has been transformed by communication technologies, journalistic narratives of migratory experiences, and the complex relationships between private and public spaces of consumption and belonging. This book shows how seemingly disparate sites of experience and representation-call centers, newspapers, shopping malls, and literature-can reveal the complicated process of a nation reinventing itself.